Seasonal Diet and Prey Preference of the African Lion in a Waterhole-Driven Semi-Arid Savanna - Davidson, Zeke; Valeix, Marion; Van Kesteren, Freya; Loveridge, Andrew J.; Hunt, Jane E.; Murindagomo, Felix; Macdonald, David W. (PLOS ONE, 2013)
Large carnivores inhabiting ecosystems with heterogeneously distributed environmental resources with strong seasonal variations frequently employ opportunistic foraging strategies, often typified by seasonal switches in diet. In semi-arid ecosystems, herbivore distribution is generally more homogeneous in the wet season, when surface water is abundant, than in the dry season when only permanent sources remain. Here, we investigate the seasonal contribution of the different herbivore species, prey preference and distribution of kills (i.e. feeding locations) of African lions in Hwange National Park, Zimbabwe, a semi-arid African savanna structured by artificial waterholes. We used data from 245 kills and 74 faecal samples. Buffalo consistently emerged as the most frequently utilised prey in all seasons by both male (56%) and female (33%) lions, contributing the most to lion dietary biomass. Jacobs’ index also revealed that buffalo was the most intensively selected species throughout the year. For female lions, kudu and to a lesser extent the group “medium Bovidae” are the most important secondary prey. This study revealed seasonal patterns in secondary prey consumption by female lions partly based on prey ecology with browsers, such as giraffe and kudu, mainly consumed in the early dry season, and grazers, such as zebra and suids, contributing more to female diet in the late dry season. Further, it revealed the opportunistic hunting behaviour of lions for prey as diverse as elephants and mice, with elephants taken mostly as juveniles at the end of the dry season during droughts. Jacobs’ index finally revealed a very strong preference for kills within 2 km from a waterhole for all prey species, except small antelopes, in all seasons. This suggested that surface-water resources form passive traps and contribute to the structuring of lion foraging behaviour.